Examining supply chain relationships: Do buyer and supplier perspectives on collaborative relationships differ? - Nyaga, Gilbert N.; Whipple, Judith M.; Lynch, Daniel F. (Journal of Operations Management, 2010)
Firms are building collaborative relationships with their supply chain partners in order to achieve efficiencies, flexibility, and sustainable competitive advantage. However, it is unclear if collaborative relationships provide benefits that compensate for the additional expense associated with such relationships. Further, it is unclear what factors promote successful collaborations. This research examines collaborative relationships in two separate studies using structural equation modeling: one study examines buyers’ perceptions and the second study examines suppliers’ perceptions. The two studies are then compared using invariance testing in order to determine economic and relational factors that drive satisfaction and performance from each party's perspective. Results show that collaborative activities, such as information sharing, joint relationship effort, and dedicated investments lead to trust and commitment. Trust and commitment, in turn, lead to improved satisfaction and performance. Results from the two independent studies exhibit similarities and differences; while the conceptual model is highly similar, certain paths vary in their significance and/or their importance across buyer and supplier firms such that buyers focus more on relationship outcomes while suppliers look to safeguard their transaction specific investments through information sharing and joint relationship effort. Managerial and theoretical implications of the findings are discussed.